2021
DOI: 10.1002/app.51515
|View full text |Cite
|
Sign up to set email alerts
|

Improving gas barrier properties of sugarcane‐based LLDPE with cellulose nanocrystals

Abstract: This study was aimed at improving the gas barrier property of sugarcane based LLDPE using cellulose nanocrystals (CNCs). Specifically, this study evaluated the effect of CNC content on the crystallinity, tortuosity factor, carbon dioxide permeability (P CO2 ), and/or oxygen permeability (P O2 ) of bio-LLDPE sheets and films. All nanocomposites showed considerable improvement in gas barrier irrespective of the CNC content. The P CO2 coefficient of LLDPE sheets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
(207 reference statements)
0
8
0
Order By: Relevance
“…23 In a recent study, gas barrier property was improved by fabricating cellulose nanocrystals/LLDPE composites. 24 These above mentioned experiments did not consider waste materials while fabricating composite films. Hence, a novel strategy was taken to fabricate composite films from LS and LB combined with LLDPE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In a recent study, gas barrier property was improved by fabricating cellulose nanocrystals/LLDPE composites. 24 These above mentioned experiments did not consider waste materials while fabricating composite films. Hence, a novel strategy was taken to fabricate composite films from LS and LB combined with LLDPE.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin‐based composite films with LLDPE were fabricated, resulting in improved mechanical strength, thermal stability, and environmental safety 23 . In a recent study, gas barrier property was improved by fabricating cellulose nanocrystals/LLDPE composites 24 . These above mentioned experiments did not consider waste materials while fabricating composite films.…”
Section: Introductionmentioning
confidence: 99%
“…178 Therefore, the transmittance can be used as an indicator of CNC dispersion in the matrix. 229 Geng et al found that the addition of CNCs did not affect the transmittance of the composite films, and all the obtained composites showed high transmittance, indicating the nanoscale dispersion of CNCs. 115 Several works have reported similar results.…”
Section: Interface Representationmentioning
confidence: 98%
“…In general, the addition of CNCs does not affect the transmittance of the composites when the CNCs are well dispersed, and their particle size is smaller than the wavelength of visible light (400–800 nm) . Therefore, the transmittance can be used as an indicator of CNC dispersion in the matrix . Geng et al found that the addition of CNCs did not affect the transmittance of the composite films, and all the obtained composites showed high transmittance, indicating the nanoscale dispersion of CNCs .…”
Section: Indirect Evaluationmentioning
confidence: 99%
“…One of them, linear low-density polyethylene (LLDPE), has decent impact resistance and tensile strength [ 41 ]. LLDPE has low crystallinity, which contributes to its excellent transparency [ 42 ]. LLDPE’s applicability is nonetheless constrained because it is a nonpolar polymer with an inert surface and low surface energy.…”
Section: Introductionmentioning
confidence: 99%